2022
DOI: 10.3390/microorganisms10081605
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and Physiology of Akkermansia muciniphila Isolates from Human Intestine Reveal Specialized Mucosal Adaptation

Abstract: Akkermansia muciniphila is a champion of mucin degradation in the human gastrointestinal tract. Here, we report the isolation of six novel strains from healthy human donors and their genomic, proteomic and physiological characterization in comparison to the type-strains A. muciniphila MucT and A. glycaniphila PytT. Complete genome sequencing revealed that, despite their large genomic similarity (>97.6%), the novel isolates clustered into two distinct subspecies of A. muciniphila: Amuc1, which includes the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
2
4
0
Order By: Relevance
“…Their results showed that DSM 22959 T is resistant to gentamicin, kanamycin, streptomycin, and ciprofloxacin, consistently with our findings. Furthermore, we found our results in line with the EFSA 2021 document 20 and Ouwerkerk et al 45 , where authors reported that A. muciniphila BAA-835 (= DSM 22959 T ) presented high resistance levels to aminoglycosides, and ciprofloxacin similarly to other A. muciniphila strains.…”
Section: Resultssupporting
confidence: 91%
“…Their results showed that DSM 22959 T is resistant to gentamicin, kanamycin, streptomycin, and ciprofloxacin, consistently with our findings. Furthermore, we found our results in line with the EFSA 2021 document 20 and Ouwerkerk et al 45 , where authors reported that A. muciniphila BAA-835 (= DSM 22959 T ) presented high resistance levels to aminoglycosides, and ciprofloxacin similarly to other A. muciniphila strains.…”
Section: Resultssupporting
confidence: 91%
“…Meanwhile, analysis of the genome sequences indicated that A. muciniphila DSM 22959 posed little risk of ARG horizontal transfer because there is no mobile genetic elements detected within its genome. Similar results were reported for the type-strain Muc T and human isolates of A. muciniphila, intrinsic resistance genes observed seem to pose no risks by determining their antibiotic resistance phenotype, and there is no significant risk for the horizontal transfer of ARGs (Ouwerkerk et al, 2022). These results indicated the ARGs of A. muciniphila might pose a small risk of transmission.…”
Section: Antibiotic Resistance Characteristics Of Akkermansia Mucinip...supporting
confidence: 83%
“…On the other hand, we observed a decrease of short chain fatty acids (SCFAs) producers, like Anaerostipes, Ruminococcus, Blautia, Coprococcus , Bifidobacterium, Barnesiella and Akkermansia 30 32 . These bacteria have anti-inflammatory properties and their decrease could contribute to functional dysbiosis.…”
Section: Discussionmentioning
confidence: 90%